BEZPIECZEŃSTWO OBROTU PRAWNO- -FINANSOWEGO. OBOWIĄZKI NOTARIUSZA W ŚWIETLE USTAWY O PRZECIWDZIAŁANIU PRANIU PIENIĘDZY ORAZ FINANSOWANIU TERRORYZMU - Holocher, Justyna (Kwartalnik Prawa Publicznego, 2016)
The law on the prevention of money laundering and terrorist financing determines the principles and the procedure aimed at preventing money laundering and terrorist financing, the use of special restrictive means against persons and groups and eventually, the duties of subjects who participate in financial transactions, notaries public included. The responsibilities of the notary public, arising from the model of notarial institution and boiling down to guarantee the security of legal transactions have been supplemented with the following duties: registration of transactions, sending information to the GIIF (General Inspector of Financial Information) and notary public’being subject to inspections. Since the very beginning this regulation by law has been raising doubts which regard not only the rules themselves, their legitimacy and effectiveness, but also the wording of the text. The reason for the controversies concerning this law is that within his/her responsibilities, the notary public is not obliged either to ascertain whether the money is of criminal origin or to verify his/her transactions in view of money laundering of financing of terrorism. The notary public has neither legal nor practical measures to adopt in this field; moreover, the State offers neither money nor any financial coparticipation in performing such tasks. In addition, in the course of legal transactions, the notary’s professional secrecy might be infringed, which means breach of professional confidentiality as well. In view of such objections, of particular doubt is the possible pecuniary penalty provided either for failing or incorrect application of the law, all the more so because those items are inaccurate and in defiance of the principles of law making techniques.